Banks and Sovereigns: Did Adversity Bring Them Closer? - Mardi H. Dungey; Thomas Flavin; Lisa Sheenan (Queen's University Belfast, Queen's Management School, 2020)
We analyse the stability of the cross-market shock transmission mechanism between banks and sovereign bonds during the Eurozone sovereign debt crisis for crisis-hit periphery countries and Germany. We also examine the shock propagation of banking shocks and sovereign bond shocks between domestic and external markets. Using a Markov-switching framework, we find strong evidence of bilateral contagion between banks and sovereign bonds and also between domestic and external banking sectors. Sovereign bond markets are different. An external shock only produces contagious effects in Greece, who were largely dependent on external aid. For all the others, external shocks lead to decoupling as investors became increasingly discerning in their perception of the debt instruments issued by different Eurozone states
Keywords: G01; G10; G21; 330